Dynamics of the Soviet politics (Cambridge, 1976)
The Dynamics of Soviet Politics is the result of reflective and thorough research into the centers of a system whose inner debates are not open to public discussion and review, a system which tolerates no public opposition parties, no prying congressional committees, and no investigative journalists to ferret out secrets. The expert authors offer an inside view of the workings of this closed system a view rarely found elsewhere in discussions of Soviet affairs. Their work, building as it does on the achievements of Soviet studies over the last thirty years, is firmly rooted in established knowledge and covers sufficient new ground to enable future studies of Soviet politics and social practices to move ahead unencumbered by stereotypes, sensationalism, or mystification.
Keywords: RussiaPolitics And Govt.-1953.